Cinsiyetçi Milliyetçilik ve Savaşlarda Cinsel Şiddetin Kullanımı: Bosna Örneği - Tuğçe Kelleci (Alternatif Politika, 2017)
In this article, the construction process of gendered identity within the context of ethnic conflicts is discussed, and sexual violence during the Bosnian War is analyzed as a case study. Feminism discusses women’s control and repression by masculine thought and practices through social, political, ideological and international dimensions, and studies the facts such as war, nationalism, militarism and foreign policy within the framework of power relations. A state-centric analysis of these facts overshadows the ideological and sociological dimensions of the acts of violence toward individuals/groups and makes it difficult to find out the motivations and discourses behind the rapes during the wars.